2016
DOI: 10.2485/jhtb.25.195
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Signaling Pathway Activation via TGF-β Differs in the Anterior and Posterior Axis During Palatal Development

Abstract: It is important to understand the different mechanisms involved in anterior hard and posterior soft palate development to prevent and treat patients with cleft palate. Genetic analyses of humans and genemutated mice with cleft palate have shown that TGF-β signaling has a critical role in palatogenesis. However, the intracellular signaling pathway of TGF-β during palatogenesis in the anterior-posterior axis has not yet been fully understood. In the present study, the expression patterns of intracellular molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Although TGF-β signaling is recognized to have particular significance in the posterior palatal mesenchyme, TGF-β3 is expressed continuously throughout the entire palatal epithelium (Taya et al, 1999). Furthermore, we have reported that Smad2 and Smad3, which are transcriptional factors involved in TGF-β signaling, are also activated in the palatal epithelium throughout the entire anterior-posterior axis (Higa et al, 2016). However, the phenotype of mice with conditional knockout of the TGF-β type I receptor (K14-cre;Tgfbr1 fl/fl ) and TGF-β type II receptor (K14-cre;Tgfbr2 fl/fl ) in the palatal epithelium is partial cleft of the posterior palatal shelves, with no developmental abnormality of the anterior portion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TGF-β signaling is recognized to have particular significance in the posterior palatal mesenchyme, TGF-β3 is expressed continuously throughout the entire palatal epithelium (Taya et al, 1999). Furthermore, we have reported that Smad2 and Smad3, which are transcriptional factors involved in TGF-β signaling, are also activated in the palatal epithelium throughout the entire anterior-posterior axis (Higa et al, 2016). However, the phenotype of mice with conditional knockout of the TGF-β type I receptor (K14-cre;Tgfbr1 fl/fl ) and TGF-β type II receptor (K14-cre;Tgfbr2 fl/fl ) in the palatal epithelium is partial cleft of the posterior palatal shelves, with no developmental abnormality of the anterior portion.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the developmental stages for analysis on the basis of previous reports (Oka et al, 2012;Higa et al, 2016). The palatal shelves are evident on either side of the tongue at E13.5 and are elevated above the tongue at around E14.0.…”
Section: Palatal Development Stagesmentioning
confidence: 99%